Can therapeutic strategies prevent and manage dyskinesia in Parkinson's disease? An update. Issue 12 (2nd December 2019) - Leta, Valentina; Jenner, Peter; Chaudhuri, K. Ray; Antonini, Angelo
ABSTRACT: Introduction : Dyskinesia is a motor complication of Parkinson's disease (PD) characterized by clinical heterogeneity and complex pathogenesis and associated with long-term levodopa therapy. Recent and controversial views on the management of PD patients have suggested that overall dyskinesia rates, and particularly troublesome dyskinesia, may be declining due to more conservative levodopa dosing regimens, widespread availability and early introduction of deep brain stimulation, and use of continuous drug delivery strategies. Nevertheless, anti-dyskinetic agents continue to be evaluated in clinical trials and recent efforts have focused on non-dopaminergic drugs. Areas covered : In this review, the authors discuss the clinical phenomenology and current understanding of dyskinesia in PD with a focus on up-to-date therapeutic strategies to prevent and manage these drug-related involuntary movements. Expert opinion : The way dyskinesia in PD is currently managed should be changed and attention should be focused toward a more personalized medicine rather than a one-fits-all-approach. The correct identification of dyskinesia types and tailored treatments are crucial for a better management of these involuntary movements together with a holistic approach which considers additional influencing factors. The future for dyskinesia treatment is likely to be found in non-dopaminergic approaches, first set into motion by the introduction of amantadine.